Development of guidelines for occupational therapy in Huntington''s disease. (February 2012) - Cook, Clare; Page, Kirsty; Wagstaff, Anne; Simpson, Sheila A; Rae, Daniela
SUMMARY This paper introduces the 'Guidelines for Occupational Therapists working with people with Huntington''s disease'' which is currently being developed by the European Huntington''s Disease Network (EHDN) Standards of Care Occupational Therapists working group. This article aims to describe the everyday functional problems experienced by people with Huntington''s disease, the role of the occupational therapist, the systematic literature review which preceded the formulation of the guidelines and use excerpts from the guideline to illustrate some of the issues raised.